2000
DOI: 10.1093/jnen/59.7.628
|View full text |Cite
|
Sign up to set email alerts
|

Infiltration of Hematogenous Lineage Cells Into the Demyelinating Central Nervous System of Twitcher Mice

Abstract: Infiltration of hematogenous lineage cells into the central nervous system (CNS) was investigated in the twitcher mouse, a murine model of globoid cell leukodystrophy in human. The hematogenous cells were selectively labeled following intraperitoneal injection of rhodamine isothiocyanate (RhIc). The frequency of detecting Rhlc-labeled cells (Rhlc+ cells) in the twitcher CNS varied with age. RhIc+ cells were hardly detected when injection was made prior to the postnatal day (PND) 30. The number of Rhlc' cells i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 38 publications
4
32
0
Order By: Relevance
“…This procedure has been implemented with promising results in other animal models of LSDs. 23,[55][56][57][58] It is becoming increasingly clear, however, that individual LSDs respond differently to the same therapeutic paradigm, most likely because of the nature of the enzyme defect, the accumulated products, and their combined effect on cell metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This procedure has been implemented with promising results in other animal models of LSDs. 23,[55][56][57][58] It is becoming increasingly clear, however, that individual LSDs respond differently to the same therapeutic paradigm, most likely because of the nature of the enzyme defect, the accumulated products, and their combined effect on cell metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15] In the CNS, chemokines are expressed constitutively at low or negligible levels in astrocytes and microglia, but their expression is rapidly induced by neuroinflammatory conditions [16][17][18] and is mediated by several proinflammatory cytokines (eg, tumor necrosis factor ␣ [TNF-␣], interferon ␥ [IFN-␥], and tumor growth factor ␤1 [TGF-␤1]). [19][20][21][22] CNS inflammation occurs in several neurodegenerative conditions, including those associated with a lysosomal storage disease (LSD), [23][24] and is likely responsible for the recruitment of monocytes and macrophages from peripheral blood. In the murine model of the LSD, G M2 -gangliosidosis recruitment of macrophages into the CNS is mediated by the chemokine macrophage inflammatory protein 1-␣ (MIP-1␣) and has been implicated in the pathogenesis of this disease.…”
mentioning
confidence: 99%
“…Neuroinflammation is implicated in the progressive nature of several neurodegenerative diseases and is described in almost all LSDs with neurological involvement (21)(22)(23)(24)(25)(26)(27). However, it is still unclear whether macrophage and astrocyte activation in LSDs is triggered by their intracellular storage or represents a response to neuronal damage.…”
Section: Lysosomal Storage In Neurons Elicits Neuroinflammation In Msdmentioning
confidence: 99%
“…The absence of MHC class II molecules reduces CNS demyelination and microglial/macrophage infiltration in the twitcher brain (Matsushima et al, 1994). It has also been reported that there is expression of proinflammatory molecules, such as interleukin-6 (IL-6), tumor necrosis factor ␣ (TNF␣) (LeVine and Brown, 1997), monocyte chemoattractant protein-1, interferon-induced protein-10, macrophage inflammatory protein-1␣ (MIP-1␣), MIP-1␤, and RANTES (regulated on activation normal T-cell expressed and secreted) (Wu et al, 2000) in twitcher. Furthermore, we recently reported that TNF␣ expression increased with the progression of demyelination in twitcher and that a TNF␣ inhibitor suppresses such demyelination (Kagitani-Shimono et al, 2005).…”
Section: Introductionmentioning
confidence: 99%